2021
DOI: 10.1007/s00268-021-06073-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Visceral Obesity, Sarcopenia and Sarcopenic Obesity on Surgical Outcomes After Liver Resections for Colorectal Metastases

Abstract: Background The impact of body compositions on surgical results is controversially discussed. This study examined whether visceral obesity, sarcopenia or sarcopenic obesity influence the outcome after hepatic resections of synchronous colorectal liver metastases. Methods Ninety-four consecutive patients with primary hepatic resections of synchronous colorectal metastases were identified from a single center database between January 2013 and August 2018. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 55 publications
3
35
0
Order By: Relevance
“…Sarcopenia, or the involuntary loss of skeletal muscle, has been associated with risk for mortality in patients with various primary malignant neoplasms such as pancreatic, gastric, breast, and lung cancer, in addition to patients suffering from metastatic disease. [36][37][38] The underlying mechanism that links sarcopenia to mortality in patients with malignant disease has not been well defined. Various candidate mechanisms for muscle wasting have been described-ranging from muscle catabolism due to systemic inflammation, to the inhibition of myoblast differentiation caused by an uninhibited release of the negative muscle cell differentiation regulator, myostatin.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia, or the involuntary loss of skeletal muscle, has been associated with risk for mortality in patients with various primary malignant neoplasms such as pancreatic, gastric, breast, and lung cancer, in addition to patients suffering from metastatic disease. [36][37][38] The underlying mechanism that links sarcopenia to mortality in patients with malignant disease has not been well defined. Various candidate mechanisms for muscle wasting have been described-ranging from muscle catabolism due to systemic inflammation, to the inhibition of myoblast differentiation caused by an uninhibited release of the negative muscle cell differentiation regulator, myostatin.…”
Section: Discussionmentioning
confidence: 99%
“…Both experimental and clinical analyses have demonstrated an impaired response to treatment and an impaired overall survival in patients with a reduced muscle mass and/or an impaired muscle quality [ 17 ]. Nevertheless, many questions including the magnitude of the associations and whether parameters that have been established in patients receiving surgery can be translated to patients in palliative disease stages have remained unanswered [ 18 ]. Here, we demonstrate that routine CT scans can be used to easily assess sarcopenia as well as myosteatosis in patients receiving palliative therapy for advanced-stage CCA and that both parameters represent prognostic markers for OS.…”
Section: Discussionmentioning
confidence: 99%
“…Few mechanisms have been explored in humans that interrogate how visceral adiposity modulates tumor biology [ 51 , 53 , 54 ]. As alluded to earlier in this review, obesity appears to be protective for survival in lung cancer.…”
Section: Obesity's Link To Insulin Resistance and Hyperinsulinemiamentioning
confidence: 99%
“…Sarcopenic skeletal muscles are known to be insulin resistant even in the setting of low whole-body fat stores [ 70 ], and considering that skeletal muscle is a primary site of both insulin action and glucose uptake/storage [ 71–75 ], sarcopenia contributes significantly to systemic metabolic syndrome [ 76 ]. Numerous studies have shown detrimental epidemiological consequences of sarcopenic obesity on cancer incidence, progression, and survival, with the largest influence on cancer incidence [ 53 , 54 , 69 , 77–81 ]. Likely mechanisms of sarcopenia-associated insulin resistance include reduced mitochondrial function (i.e.…”
Section: Obesity's Link To Insulin Resistance and Hyperinsulinemiamentioning
confidence: 99%